The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.3390/jcm9113405
|View full text |Cite
|
Sign up to set email alerts
|

Executive Functions Are Associated with Fall Risk but not Balance in Chronic Cerebrovascular Disease

Abstract: Background: Older people’s deficits in executive functions (EF) have been shown to lead to higher fall risk, postural sway, and reduced speed. Crucially, EF impairments are even more pronounced in individuals with chronic cerebrovascular disease (CVD), namely vascular cognitive impairment. Methods: In this retrospective cross-sectional study, we used a complete neuropsychological battery, including the Trail Making Test (TMT) and physical measures, such as the Morse fall and EQUI scales, to assess 66 individua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
2

Relationship

3
2

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 53 publications
(97 reference statements)
0
6
0
Order By: Relevance
“…Recently, associations between measures of motor and cognitive abilities have been reported in older individuals with atrial fibrillation, although these relationships were not related to cerebral lesion burden [42]. In chronic cerebrovascular disease, executive functions, but not global cognition, has been associated with risk of falls, while balance had no correlations with neuropsychological measures [43].…”
Section: Ta B L Ementioning
confidence: 99%
“…Recently, associations between measures of motor and cognitive abilities have been reported in older individuals with atrial fibrillation, although these relationships were not related to cerebral lesion burden [42]. In chronic cerebrovascular disease, executive functions, but not global cognition, has been associated with risk of falls, while balance had no correlations with neuropsychological measures [43].…”
Section: Ta B L Ementioning
confidence: 99%
“…The risk of cognitive and motor decline is high in healthy, frail, and multimorbid older adults (>65 years) and people living with dementia [15][16][17][18][19][20]. In addition, normal and pathological aging are characterized by a decline in dual-task ability [8,10,20].…”
Section: Discussionmentioning
confidence: 99%
“…This reduced ability can have serious consequences (eg, falls and injuries) for older adults [2]. Parallel to this, older adults aged ≥65 years with and without frailty or chronic diseases (eg, multimorbidity and dementia) are at great risk for falls and cognitive decline [15][16][17][18][19][20].…”
Section: Introductionmentioning
confidence: 99%
“…17 In chronic cerebrovascular disease, executive functions, but not global cognition, has been associated with risk of falls, while balance had no correlations with neuropsychological measures. 16 The role of WMH in old-age disability in terms of impaired IADL has been well documented. 3 We observed both WMH and GM volumes to be associated with IADL as evaluated with a validated questionnaire by the patient's close informant.…”
Section: Discussionmentioning
confidence: 99%
“…A recent retrospective study has reported executive functions, but not global cognition, to be associated with risk of falls in patients with chronic cerebrovascular disease, but it did not demonstrate any relationship between measures of cognition and balance. 16 Another study has found an association between mobility and cognitive performance independently of cerebral lesion burden among older patients with atrial fibrillation. 17 This study investigated the relationships and functional significance of cognitive and motor abilities in older individuals with different degrees of WMH by using standard physical and neuropsychological assessments and quantitative evaluation of brain changes on structural MRI.…”
Section: Introductionmentioning
confidence: 99%